Effect of solidification time to the wall thickness created on the slush casting product - Tengku Ahmad Firdaus, Tengku Zainal (2009)
Casting is most often used for making complex shapes that would be otherwise difficult or uneconomical to make by other methods is a manufacturing process by which a liquid material is usually poured into a mold, which contains a hollow cavity of the desired shape, and then allowed to solidify. After a certain time, the excess liquid will poured out, and then the solid casting is then ejected or broken out to complete the process. Casting may be used to form various materials that cold set after mixing of components (such as epoxies, concrete, plaster and clay Therefore, this study is conducted to fabricate the tool holder by using rubberwood as the material for the pattern, RTV-2 silicone rubber for the mould and polyester resin for product. The main objective of this study is to to study the effect of solidification time to the wall thickness created on the slush casting product to suit the function of product and find the optimum solidification time to achieve desire wall thickness for particular slush casting product. The study parameters are based on slush casting solidification time, which are 1, 2, 3, 4 and 5 minutes. The study output is wall thickness and digital vernier caliper is used to measure the dimension of wall thickness. Based on the measurement, only product have the value factor of safety (FOS) more than one, >1 is selected as a product. Based on the study analysis, it is discovered that the highest solidification time produce the highest wall thickness created on the product.